Kajian Numerik Pengaruh Push dan Pull Velocity terhadap Pola Aliran Pada Downward Push-Pull Air Curtain - Piero Wahyu Iskandar; Burniadi Moballa; Muh Anis Mustaghfirin (Proceedings Conference on Marine Engineering and its Application, 2023)
Transmission of COVID-19 is still increasing in the world, such as in China andIndonesia. One of the reasons for the increasing number of positive cases of COVID-19 isthe occurrence of transmission from industrial clusters, the implementation of a minimumsocial distancing of 1 to 2 meters between workers is difficult to do. This is due to limitationsin layout, area, and industrial work systems. Thus, a system is needed to protect industrialworkers from potential exposure to COVID-19. One technology that has high potential to beapplied is air curtain. From these problems, this research will carry out an analysis of theoptimum push-pull discharge and air velocity, and the regime map for downward push-pullair curtain, the method used to carry out the analysis is Computional Fluid Dynamics (CFD)where the stages of the CFD process are preprocessing, processing, postprocessing. Thesoftware used to complete this final project is SALOME for the preprocessing,, OpenFOAMfor the processing, and for the postprocessing stage using ParaView. From the simulationresults that have been carried out, the results show that at a nozzle blow speed of 6,24 m/s,with a suction nozzle speed of 37,44 m/s, these are the optimum blow speed and suction nozzlevalues and are able to withstand droplet dispersion.